2006
DOI: 10.1186/1751-0147-48-25
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of hazardous dietary calcium deficiency for fattening bulls

Abstract: Background: Deficient mineral supplementation on a feedlot farm resulted in severe clinical manifestations in fattening bulls. Animals mistakenly received only 60-70% of the recommended calcium intake, while simultaneously receiving twice the amount of phosphorus recommended. Thus, the dietary Ca/P ratio was severely distorted. After approximately six months on such a diet, four fattening bulls were euthanized because of severe lameness and 15% of other animals on the farm were having clinical leg problems. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Osteoarthritis lesions occurred in more than 80% of the animals with a calcium-deficient diet (Heinola et al . 2006 ). Similarly, other authors have reported osteochondrosis-type lesions in feedlots and bull stations where the feed given was thought to be one of the causative factors (Jensen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis lesions occurred in more than 80% of the animals with a calcium-deficient diet (Heinola et al . 2006 ). Similarly, other authors have reported osteochondrosis-type lesions in feedlots and bull stations where the feed given was thought to be one of the causative factors (Jensen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondrosis in cattle is found in all types of husbandry systems, including feedlots (Davies & Munro 1999 ; Heinola et al . 2006 ; Jensen et al . 1981 ; Reiland et al .…”
Section: Introductionmentioning
confidence: 99%
“…Results of a recent study even indicated that a single ruminal acidosis event can cause a prolonged decrease in semen quality (Callaghan et al, 2014). Grain can be high in phosphorus, and diets with low calcium to phosphorus ratios have been shown to predispose to osteoarthritis and lameness (Heinola et al, 2006). Other vitamin and mineral imbalances have also been associated with osteochondritis dissecans (Davies and Munro, 1999).…”
Section: Herd-level Multivariable Model For the Postmating Bbsementioning
confidence: 99%
“…Сперматогенез у быков происходит непрерывно в течение всего года и зависит от нейрогуморальной регуляции организма и его индивидуальных особенностей. Для долголетней племенной службы быков, с сохранением хорошего качества семени, высокой половой активности, необходимо обеспечить их полноценным белком, макро и микроэлементами, витаминами [5,6]. С этой целью используются различные кормовые добавки как импортного, так и отече-ственного происхождения.…”
Section: Introductionunclassified